Okay, the first equation is already in the y=mx+b form.
Lets convert the second equation into the y=mx+b form to make it easier to solve.
6x+2y = 22
2y = -6x + 22
Divide both sides by 2
y = -3x + 11
So now you you have
y = -2x + 1
and y = -3x + 11
You can make both equations equal each other to find x
-2x +1 = -3x + 11
Solve by combining like terms
x = 10
Plug in 10 in place of either equation - just one
Lets put 10 into the first one
-2 ( 10 ) +1
y = -19
So your x and y for this problem is
(10,-19)